KEBIJAKAN KETAHANAN PANGAN BAGI PETANI MISKIN DI ERA REVOLUSI 4.0 (Program Studi Agribisnis Fakultas Pertanian Universitas Baturaja, 2020)
The era of the industrial revolution 4.0 has led to the fundamental problem of the development of the agricultural sector on a food security policy based on digitalization. The existence of an agricultural system that is not yet strong causes farmers to continue to deal with the problem of poverty. Poverty is a multi-complex problem both in terms of its causes and its implications. Poverty will cause a lack of ability to access various resources which in turn will cause the development of the agricultural sector to not work. In other words, poor farmers have the potential to produce public policies in the agricultural sector which are low accompanied by weak quality and capacity of human resources who are stakeholders in agriculture. This paper will provide a study of food security policy as an effort to overcome poverty, which is an unbroken link in overcoming the multicomplex agricultural problem in the current millennial era.